Building a voltage loss graph in the medium voltage power grid - Dang, Quang Khoa (Journal of Technical Education Science, 2011)
In the study of the plan of medium voltage power grid, it is indispensable to take into account the selection of optimal structure diagram of the grid, the wire section, and the wire length in terms of the allowed voltage loss. The topic has focused on studying and building the graph of voltage loss with the following contents: Background, reasons for building the graph of voltage loss in the medium voltage grid, research into building a program for calculation and simulation of the voltage loss graph on computer with the standard interface that is easy to use. The result has shown that it is convenient and fast to solve the problem of calculation, selection section and wire length. This also presents a new field of research, contributing to the enlargment of the theoretical basis for planning and designing medium voltage power grid